Methods to Study Mitochondria: Techniques Used to Study the Effects of Age‐Related Diseases Including Alzheimer's. Issue 1 (17th January 2023) - Baig, Javaria; Pradeepkiran, Jangampalli Adi; Reddy, P. Hemachandra
Abstract: Various laboratories across the world have developed methods to study mitochondrial proteins/markers through extraction of mitochondrial RNA and protein to assess mitophagy/autophagy in Alzheimer's disease and other age‐related diseases. Techniques outlined in this article include qRT‐PCR, immunoblotting, immunofluorescence, transmission electron microscopy, Seahorse bioanalysis, staining for mitochondrial membrane potential, detection of mitophagy, and mitochondrial functional assays. Most of these techniques have been performed in vitro (in human and mouse neuronal cell lines transfected with mutant amyloid precursor protein or tau protein cDNAs) and in vivo (in brain tissues from different mouse models of Alzheimer's and other neurological diseases). Mitochondrial abnormalities in Alzheimer's disease have taken various forms, including excessive reactive oxygen species production, mitochondrial calcium dyshomeostasis, loss of ATP, defects in mitochondrial dynamics and transport, and mitophagy. Mitochondrial dysfunction is largely involved in aging; age‐related diseases such as cancer, diabetes, and obesity; and neurodegenerative disorders including Alzheimer's disease, Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, multiple sclerosis, and others. The goal of this article is to make protocols/methods available to students, scholars, and researchers of mitochondria in order to facilitate future mitochondrial studies. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Analyzing mitochondrial gene expression in mouse brain tissue and HT22 cells by qRT‐PCR Basic Protocol 2 : Analyzing protein expression in mouse brain tissue and HT22 cells by immunoblotting Basic Protocol 3 : Immunofluorescence staining of cells and tissue sections Basic Protocol 4 : Staining for mitochondrial membrane potential Basic Protocol 5 : Assessing mitochondrial structure by transmission electron microscopy Basic Protocol 6 : Methods for detecting mitophagy Basic Protocol 7 : Bioenergetics assay via Seahorse Basic Protocol 8 : Assays for mitochondrial function